2017
DOI: 10.1093/jjco/hyx071
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular toxic effects of targeted cancer therapy

Abstract: Over the past decade, there has been a major shift in chemotherapy from non-specific cytotoxic drugs to molecular targeted drug therapies. As more molecular targeted therapies are developed, new types of cardiovascular toxicities induced by targeted therapies are a growing problem. Cardiotoxicity induced by the human epidermal growth factor receptor-2 inhibitor trastuzumab manifests as decreased left ventricular ejection fraction. In contrast to anthracycline treatment, most cardiac events occur during trastuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Chronic myeloid leukemia (CML) is a myeloproliferative disorder characterized by a genetic translocation between chromosomes 9 and 22, leading to the generation of the hybrid protein BCR-ABL with tyrosine kinase activity. For most CML patients, the introduction of BCR-ABL tyrosine kinase inhibitors (TKIs) has changed this fatal disease into a manageable chronic condition [ 1 , 2 ]. However, recent studies have revealed that patients treated with newer BCR-ABL TKIs show a significant increase in the incidence of vascular adverse events, including increased blood pressure, venous thrombosis, progressive atherosclerosis with coronary artery disease, and peripheral arterial obstructive disease [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic myeloid leukemia (CML) is a myeloproliferative disorder characterized by a genetic translocation between chromosomes 9 and 22, leading to the generation of the hybrid protein BCR-ABL with tyrosine kinase activity. For most CML patients, the introduction of BCR-ABL tyrosine kinase inhibitors (TKIs) has changed this fatal disease into a manageable chronic condition [ 1 , 2 ]. However, recent studies have revealed that patients treated with newer BCR-ABL TKIs show a significant increase in the incidence of vascular adverse events, including increased blood pressure, venous thrombosis, progressive atherosclerosis with coronary artery disease, and peripheral arterial obstructive disease [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For most CML patients, the introduction of BCR-ABL tyrosine kinase inhibitors (TKIs) has changed this fatal disease into a manageable chronic condition [ 1 , 2 ]. However, recent studies have revealed that patients treated with newer BCR-ABL TKIs show a significant increase in the incidence of vascular adverse events, including increased blood pressure, venous thrombosis, progressive atherosclerosis with coronary artery disease, and peripheral arterial obstructive disease [ 2 , 3 ]. Nilotinib, a second-generation TKI, is highly effective in the treatment of CML patients both as a first-line treatment and after imatinib treatment failure; however, it is known to be more vasculotoxic than older TKIs, including imatinib [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional chemotherapeutic drugs, such as platinum, doxorubicin, have historically been a major problem that causes cardiotoxicity. Molecular targeted therapy agents, including tyrosine kinase inhibitors (TKIs) lapatinib, sorafenib, imatinib and humanized monoclonal antibodies trastuzumab, bevacizumab, are known to cause cardiovascular toxic effects [3,4]. The recent immunotherapeutic agents such as checkpoint inhibitors (e.g., ipilimumab, nivolumab and atezolizumab), though exhibiting a highly promising therapeutic effect with durable anti-cancer responses and long-term remission in a broad spectrum of cancers, have also been found to cause cardiac dysfunction [5].…”
Section: Introductionmentioning
confidence: 99%
“…The recent immunotherapeutic agents such as checkpoint inhibitors (e.g., ipilimumab, nivolumab and atezolizumab), though exhibiting a highly promising therapeutic effect with durable anti-cancer responses and long-term remission in a broad spectrum of cancers, have also been found to cause cardiac dysfunction [5]. The common cardiac toxic effects caused by anti-cancer therapies include left ventricular dysfunction (LVD), heart failure (HF), stoke, myocardial ischemia, myocarditis, cardiomyopathy [3][4][5] and so on. For example, platinum-based compounds can induce cardiac endothelial dysfunction, leading to myocardial ischemia and stoke [6].…”
Section: Introductionmentioning
confidence: 99%